DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI DAN EKSPOR PADA KOMODITI KOPI - Niken Zahra Afifah; Rahma Indri Septiani; Riza Amelia Putri (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Climate change events are becoming a global issue affecting the agricultural sector. Climate change can reduce crop productivity, including coffee plants, especially in tropical areas that are sensitive to weather fluctuations. Climate change also affects the prevalence of diseases and pests that attack coffee plants. Increased temperatures can accelerate the life cycle of pests such as the coffee berry borer, which can cause huge losses to farmers. In addition, fungal diseases such as Hemileia vastatrix (the cause of coffee leaf spot) may increase as weather conditions change. Rising temperatures and changing rainfall patterns have a negative impact on robusta coffee productivity, especially due to heat stress, drought and pest attacks. This research emphasizes the need for the development of climate-resilient coffee varieties as well as sustainable agricultural practices to support the sustainability of coffee production in Indonesia..